2021
DOI: 10.2147/ijgm.s328332
|View full text |Cite
|
Sign up to set email alerts
|

Procedural Results and Long-Term Outcomes of Percutaneous Coronary Intervention for in-Stent Restenosis Chronic Total Occlusion Compared with de novo Chronic Total Occlusion

Abstract: Background: In-stent restenosis (ISR) chronic total occlusion (CTO) represents a challenging subgroup for revascularization of CTO by percutaneous coronary intervention (PCI). There are limited data on the treatment and outcomes of PCI for ISR CTO. Objective: We aimed to evaluate the procedural results and 2-year outcomes of PCI for ISR CTO compared with de novo CTO. Methods: Patients undergoing attempted CTO PCI between January 2017 and December 2019 were prospectively enrolled. We analyzed the procedural res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
(41 reference statements)
2
3
1
Order By: Relevance
“…As all the lesions in this study are CTOs, the patients may exhibit atypical clinical symptoms after target lesion thrombosis, making the diagnosis difficult. We observed two cases of NSTEMI (1.3%) and one cardiac death (1.9%) during the longterm follow up, which were similar to those reported in retrospective study and RCT [10,16]. The long-term follow up results in DCB only group in our study showed acceptable TLR which is comparable to DCB only strategy by other centers and slightly higher than that of DES treatment, and low rates of clinical endpoints, indicating the effect and safety of DCB only strategy in selected patients is comparable to DES implantation in native CTO lesion during long-term follow up.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As all the lesions in this study are CTOs, the patients may exhibit atypical clinical symptoms after target lesion thrombosis, making the diagnosis difficult. We observed two cases of NSTEMI (1.3%) and one cardiac death (1.9%) during the longterm follow up, which were similar to those reported in retrospective study and RCT [10,16]. The long-term follow up results in DCB only group in our study showed acceptable TLR which is comparable to DCB only strategy by other centers and slightly higher than that of DES treatment, and low rates of clinical endpoints, indicating the effect and safety of DCB only strategy in selected patients is comparable to DES implantation in native CTO lesion during long-term follow up.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we defined acceptable recanalization as TIMI flow grade 3 and residual stenosis ≤70%, and 82.5% of patients met this standard after DCB treatment. The long-term follow up showed similar results as previous CTO studies using DES [ 10 , 16 ], implying this standard might be feasible in de novo CTO lesion treated by DCB.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The final analysis included 12 studies published between 2011 to 2021, with a total of 708 391 patients: 71 353 patients underwent PCI for ISR, and 637 038 patients underwent PCI for de novo lesions. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 There was good interrater agreement between the 2 researchers performing study selection (κ=0.79; standard error=0.09) and data extraction (κ=0.81; standard error=0.06). The weighted follow‐up duration was 29.8 months.…”
Section: Resultsmentioning
confidence: 92%
“…The in-stent CTO is characterized in high lesion stenosis rate, high complexity, high di culty of opening, and special population [14,15] . The research of K. Miura et al it as the result of DES-ISR after DCB angioplasty, and the independent risk factors for RISR [7] .…”
Section: Discussionmentioning
confidence: 99%